Análise da relevância da dignidade da pessoa humana como critério delimitador da aplicação do primado do não-confisco - Furtado, Alexandre Dias de Andrade (2018)
In view of the indeterminacy of the no-confiscation concept contained in article 150, item IV, of the Federal Constitution, there is great concern about the limits of taxation not to reach the basic nucleus of protection of the individual, depriving him of a dignified life. On the other hand, without resources, it is not possible for the Social State to fulfill its obligation to provide citizens with the rights enshrined in the Federal Constitution. Social development, with the eradication of poverty and with equality between individuals, is what guides the state activity to the achievement of the project stipulated by the Original Legislator. However, the State cannot ignore the individual's ability to contribute as a limitation to the power to tax, because if it does, invariably, the state's progress will be considered confiscation. It is thus the principle of non-confiscation the last bulwark in the protection of the rights of the individual and their existence with dignity